The Influence of Work Environment, Rewards and Punishments on Work Loyalty of J&T Express Jemundo Expedition Employees, Taman District, Sidoarjo Regency - Amaliyah, Rose; Adji Kusuma, Kumara; Sumartik, Sumartik (Universitas Islam Lamongan, 2025)
This study aims to determine and measure how much influence the work environment, rewards and punishments have on work loyalty of J&T Express Jemundo Expedition Employees, Taman District, Sidoarjo Regency. This study is a quantitative study using an explanatory research approach. The population of the study includes all employees of the J&T Express Jemundo expedition company, with a total of 123 employees. The sampling process was carried out using probability sampling techniques. Data collection in this study was carried out by means of observation and distributing questionnaires measured using a Likert scale. This study uses the SPSS analysis method. Based on the results of data analysis carried out on the four hypotheses in this study, it can be concluded that the variables of the Work Environment, Rewards, and Punishment partially and simultaneously have a positive and significant influence on employee work loyalty.